APPROACHES TO EVALUATION OF RISKS AND FUNCTIONAL RESERVES OF THE CARDIOVASCULAR SYSTEM IN PATIENTS WITH MYOCARDIAL INFARCTION WITH COMORBIT PATHOLOGY, WHO ARE IN THE ACUTE PERIOD OF CARDIORABILITY - Швед, М.І.; Levytska, L.V. (World of Medicine and Biology, 2018)
With a purpose of study of possibilities of quantative assessment and probability of the influence of comorbid pathology on the course of myocardial infarction, position of functional reserves in patients with myocardial infarction and its role in the appointment of adequate individualized rehabilitation program in this category of patients, 97 patients were examined, who had acute (stationary) rehabilitation period in cardiology department. It was established that the parameters of the generally accepted hemodynamic and metabolic indicators in patients with myocardial infarction with comorbid pathology do not allow them to be used as differential diagnostic criteria for evaluating the functional reserves of the cardiovascular system. At the same time the direct correlation dependence between the presence of comorbid state and age of patients, duration of arterial hypertension, level of plasma creatinine and index of Charlson comorbid, and also a reverse correct correlation with high density lipoproteids, SPO2 and 6-minutes walking test were found. The obtained results became the basis for stratification of risks in patients, which are included in the program of rehabilitation not only by traditional markers of electrical and hemodynamic stability of the cardiovascular system, but also by the above-mentioned hidden risk factors.
Keywords: myocardial infarction; comorbid pathology; cardiorehabilitation; index of Charlson; high density lipoproteids